PRESSURE TRANSIENT ANALYSIS FOR A RESERVOIR WITH A FINITE-CONDUCTIVITY FAULT - Freddy-Humberto Escobar; Javier-Andrés Martínez; Matilde Montealegre-Madero (CT&F Ciencia, Tecnología & Futuro, 2013)
The signature of the pressure derivative curve for reservoirs with finite-conductivity faults is investigated to understand their behavior and facilitate the interpretation of pressure data. Once a fault is reached by the disturbance, the pressure derivative displays a negative unit-slope indicating that the system is connected to an aquifer, meaning dominance of steady-state flow regime. Afterwards, a half-slope straightline is displayed on the pressure derivative plot when the flow is linear to the fault. Besides, if simultaneously a linear flow occurs inside the fault plane, then a bilinear flow regime takes place which is recognized by a 1/4 slope line on the pressure derivative line. This paper presents the most complete analytical well pressure analysis methodology for finite-conductivity faulted systems using some characteristics features and points found on the pressure and pressure derivative log-log plot. Therefore, such plot is not only used as diagnosis criterion but also as a computational tool. The straight-line conventional analysis is also complemented for characterization of finite- and infinite-conductivity faults. Hence, new equations are introduced to estimate the distance to fault, the fault conductivity and the fault skin factor for such systems. The proposed expressions and methodology were successfully tested with field and synthetic cases.